Architecture and temporality in conservation philosophy: Cesare Brandi - Meraz Avila, Fidel Alejandro (2009)
In conservation of culturally significant architecture (CSA), awareness about problems of temporality and their consideration has been frequently approached with different perspectives. However, these partial explanations have usually focused on accounts of temporality that mainly approach the past and the present, and more rarely the future, but do not consider the complete spectrum of human temporality, nor explicit ontological bases. In this thesis, architecture emerges as a manifold being in constant becoming that compels human being to exercise permanently memory and assimilation. The main contribution is the proposal of an existential approach towards conservation as an intentionality grounded on the more fundamental attitudes of cultivation and care. Through epistemological and phenomenological analysis of Brandi’s thought – focusing on his paradigmatic Theory of Restoration – his attitude comes forth as a particular form of conservation intentionality limited to architecture as a work of art. Following mainly Ingarden and Ricoeur, the results of ontological and phenomenological investigations about architecture and temporality demonstrate conservation in its modern form as a limited temporal intentionality. After these theoretical pre-conditions, the existential approach applied on the previously deduced dimensions of the space and time of Dasein – in Heidegger’s terms – proved the grounding of conservation on an existential interpretation of the more fundamental notions of cultivation and care. Making an analogy with Ingarden’s notion of the architectural work of art, CSA is ontologically analysed emerging to consciousness as a manifold being that can be concretized in different ways according with the attitude of the receptor. After the phenomenological analysis of memory, architectural conservation in its modern form is demonstrated as a partial account of human temporality that can be overcome considering human inhabitation in a creative way. Partially supported on the obtained cases of remembered architecture, the hermeneutical approach concluded suggesting a solution for the impasse with an existential account of both, the artistic grounding of architecture and its characterisation as the place that temporally accompanies Dasein. Thus, architecture is ontologically demonstrated to have a manifold being in constant state of transformation that participates of an unavoidable humanised temporality, appearing as a less ambiguous object of conservation. Hence, architecture is existentially demonstrated as constituting the space for the authentically concerned human, whose temporal consciousness compels to cultivate and care about, enriching the possible approaches to conservation as a collective endeavour.